Renewable absorbents for CO2 capture: from biomass to nature. Issue 4 (16th July 2019) - He, Qingyao; Shi, Mingfei; Liang, Feihong; Xu, Lang; Ji, Long; Yan, Shuiping
Abstract: The chemical absorption process for carbon dioxide (CO2 ) capture is a promising method to reduce greenhouse gas emissions in the energy industry. Worldwide applications of the CO2 chemical absorption process will consume plenty of chemical absorbents and have hazardous impacts on the environment. The development of renewable absorbents from biomass can not only fill the gap of absorbent production, but also provide a novel green approach to recycle the used absorbents into nature without additional pollution. In this review, we summarized several renewable absorbents available from biomass such as biomass ash slurries, alkanolamines, aqueous ammonia, and amino acid salts. The preparations, CO2 absorption capacities, advanced treatments, and applications of the renewable absorbents were also reviewed. Moreover, the advantages and challenges in the preparation of the renewable absorbents were discussed, as well as their CO2 absorption performance improvement. Finally, future research avenues into degradation and utilization of renewable absorbents in nature were suggested. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.